Genetic diversity and structure of macrognathus siamensis in the Mekong river inferred from ezrad data : - Nguyen, Thi Ngoc Tran (Can Tho university, 2018)
This book introduce about Optimize EzRAD protocol in a new lab. Compare levels of genetic diversity and genetic difference between populations of M. siamensis in Hau and Tien Rivers and Paksan of Laos.